Just Transition Frames: Recognition, representation, and distribution in Irish beef farming - Murphy, Susan; Cannon, Sheila (My University, 2022)
The concept of just transition has emerged as an important governance framework guiding sectors transitioning from unsustainable to sustainable practices and is most dominant in debates on the energy transition. This research, in contrast, explores if and how this framework can make sense of the challenges facing Irish beef farming. The sector is transforming in response to an intersecting range of social, environmental, and market pressures. Beef farmers are at the centre of this, yet little research has been conducted gathering their perspectives on the changing state of their livelihoods and their concerns for the future. Here, we use a novel methodological approach, drawing on the concept of framing as a strategic communication device to explore the perspectives of key actors in this sector and a multi-dimensional environmental justice framework to identify the elements of (in)justice present within frames. This novel just transition frames and functions model exposes how misalignment between powerful key actors, concerned with distributional matters, and beef farmers, concerned with declining social status, shifting identities, and under-representation is found to be contributing to conflict. We show how the application of this model can inform pathways to just and sustainable futures.
PUBLISHED
Keywords: Just transition; Environmental justice; Issue framing; Beef farming; Climate change; Sustainability